Femmes fatales, saints, empowered women: Female biopics in Italian public television. Issue 2 (2nd January 2023) - Buonanno, Milly
Joining the current scholarly dialogue between biopic studies and gender/feminist/media studies, this work is meant to retrace the evolution of gender politics as expressed in the biographical genre which has played the role of the mainstay of domestic television drama since the origin of Italian broadcasting. Through a historical perspective that aims to track continuity and change over time, this work places a major focus on the 2000s, during which time women's biographies experienced considerable growth on Italian television and more importantly began to replace traditional figures of saints and femmes fatales with female professionals in positions of leadership (journalists, politicians, entrepreneurs, scientists and artists). Based on the examination of several biopics and the close analysis of the most watched recent biopic about an 'empowered woman' ( Luisa Spagnoli [2016]), this article seeks to explore whether the new wave of female biopics breaks crystallized generic conventions and foregrounds new representational strategies influenced by feminism or post-feminism.